2013 10th IEEE International Conference and Workshops on Automatic Face and Gesture Recognition (FG) 2013
DOI: 10.1109/fg.2013.6553748
|View full text |Cite
|
Sign up to set email alerts
|

Social risk and depression: Evidence from manual and automatic facial expression analysis

Abstract: Investigated the relationship between change over time in severity of depression symptoms and facial expression. Depressed participants were followed over the course of treatment and video recorded during a series of clinical interviews. Facial expressions were analyzed from the video using both manual and automatic systems. Automatic and manual coding were highly consistent for FACS action units, and showed similar effects for change over time in depression severity. For both systems, when symptom severity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 52 publications
2
98
0
3
Order By: Relevance
“…Based on these techniques, the automatic analysis of spontaneous facial expressions in the wild is one key topic in affective computing. The target affective states include prototypical emotions [44], emotional dimensions such as valence and arousal [32], empathy [23], pain [29,27], and depression [19]. Some of them have focused on the observers' impressions about the target person [32,23], like the present study.…”
Section: Related Workmentioning
confidence: 99%
“…Based on these techniques, the automatic analysis of spontaneous facial expressions in the wild is one key topic in affective computing. The target affective states include prototypical emotions [44], emotional dimensions such as valence and arousal [32], empathy [23], pain [29,27], and depression [19]. Some of them have focused on the observers' impressions about the target person [32,23], like the present study.…”
Section: Related Workmentioning
confidence: 99%
“…The analysis of spontaneous facial expressions in the wild is currently a key topic in affective computing. The target affective states include prototypical emotions [Valstar et al 2011], emotional dimensions such as valence and arousal [McKeown et al 2010], empathy [Kumano et al 2012], pain [Lucey et al 2012;Littlewort et al 2007], and depression [Girard et al 2013]. Some works have focused on the observers' impressions about the target person [McKeown et al 2010;Kumano et al 2012], such as the present study.…”
Section: Related Workmentioning
confidence: 98%
“…[35,8]. More recently, Girard et al [12] performed a longitudinal study of manual and automatic facial expressions during semistructured clinical interviews of 34 clinically depressed patients. They found that for both manual and automatic facial muscle activity analysis, participants with high symptom severity produced more expressions associated with contempt, smile less, and the smiles that were made were more likely to be related to contempt.…”
Section: Mood and Anxiety Disordersmentioning
confidence: 98%